Hybrid isoquinolines from Thalictrum foetidum: a new type of aporphine inhibiting Staphylococcus aureus by combined mechanisms. Issue 19 (9th September 2019) - Ding, Cai-Feng; Zhang, Rong-Ping; Yu, Hao-Fei; Yang, Jing; Qin, Xu-Jie; Dai, Zhi; Liu, Ya-Ping; Lu, Qiu-Min; Lai, Ren; Luo, Xiao-Dong
Abstract : Thalfoetines A–D (1–4 ), unique hybrid aporphine alkaloids with a C-7 aromatic unit formed by a new C–C bond linking two building blocks, were isolated from Thalictrum foetidum . Abstract : Thalfoetines A–D (1–4 ), unique hybrid aporphine alkaloids with a C-7 aromatic unit formed by a new C–C bond linking two building blocks, were isolated from Thalictrum foetidum . Their structures were elucidated by extensive spectroscopic and computational analysis. They inhibited bacteria significantly, and compound 1 damaged the cell structure of Staphylococcus aureus and inhibited its DNA synthesis.